Strengthening Interfaith Dialogue through Religious Moderation Discourse: An African Perspective - Majemu, Shefiu Abdulkareem (International Journal of Civilizations Studies & Tolerance Sciences, 2024)
This paper aims to demonstrate how religions moderation can help strengthen inter-religious dialogue and peace-building processes in Africa. The African context of violent-extremism and radicalization is quite different from what is obtainable in other part of the world. The paper focuses more on the root causes, drivers and motivations of radicalization and violent extremism in Africa and thereby proffer sustainable solutions among which religious moderation is tangential to reducing the negative narratives propounded and used by perpetrators. This paper will provide a brief introduction to the terms interfaith dialogue, peace-building, religious moderation discourse, radicalization, violent extremism and terrorism: and will present various ways they have been defined in existing academic literature and policy document. It will further explain the nexus between interfaith dialogue and religious moderation, and provide practical ways of reducing violent extremism, radicalization and extremism in other to foster sustainable peace in Africa.